Ruxolitinib Treatment During Myelofibrosis Leads to Cutaneous Mycobacterium marinum Infection: A Case Report - Chen X; Zhang D; Wang T; Ma W (Dove Medical Press, 2023)
Xiaonan Chen,1 Dong Zhang,2 Teng Wang,3 Weiyuan Ma2 1Department of Hematology, Affiliated Hospital of Weifang Medical University, Weifang, People's Republic of China; 2Department of Dermatology, Affiliated Hospital of Weifang Medical University, Weifang, People's Republic of China; 3Department of Orthopedics, Qilu Hospital of Shandong University, Jinan, People's Republic of ChinaCorrespondence: Teng Wang, Qilu Hospital of Shandong University, Jinan, People's Republic of China, Tel +86-531-82169361, Email wt10113277@163.com Weiyuan Ma, Department of Dermatology, Affiliated Hospital of Weifang Medical University, Weifang, People's Republic of China, Tel +86-536-3081272, Email fymaweiyuan@wfmc.edu.cnAbstract: Mycobacterium marinum is an atypical bacterium, and skin infections caused by it are relatively rare, usually occurring in workers engaged in seafood processing and housewives who clean and prepare fish for consumption. The infection often occurs after the skin is punctured by fish scales, spines, etc. The JAK/STAT signaling pathway is closely related to the human immune response to infections. Therefore, JAK inhibitors may induce and exacerbate various infections in clinical practice. This article reports a case of mycobacterium marinum skin infection in the left upper limb of a female patient with chronic idiopathic myelofibrosis during treatment with ruxolitinib. The patient denied being punctured or scratched by fish scales or spines. Clinical manifestations included multiple infiltrative erythemas and subcutaneous nodules in the thumb and forearm. Histopathological examination showed infiltration of mixed acute and chronic inflammatory cells in the subcutaneous tissue. The diagnosis was ultimately confirmed by NGS sequencing. The patient was cured after taking moxifloxacin and clarithromycin for 10 months. Infection is a common adverse reaction of JAK inhibitors, but no literature has reported on mycobacterium marinum skin infections occurring during JAK inhibitor treatment, which is relatively rare. As the clinical application of JAK inhibitors becomes more widespread, the skin infections they cause may present in various forms and require the attention of clinicians.Keywords: ruxolitinib, JAK inhibitors, Mycobacterium marinum, skin, infection